Optimalisasi Media Berbasis Visual dalam Upaya Meningkatkan Pemahaman Belajar PPKn di Kelas Rendah SD Muhammadiyah 1 Kisaran - Muhammad Fadillah Iqbal Purba; Nadya Utami Samosir; Husnia Aqilah; Adam Ar Rasyid; Fadhli Ihsan Arbas Hasibuan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The low level of understanding of Pancasila and Citizenship Education (PPKn) among lower-grade students remains a challenge because learning tends to use conventional methods that are less able to concretize concepts and attract students' attention. This study aims to describe the implementation of visual-based media and analyze its contribution to improving PPKn learning comprehension among lower-grade students at Muhammadiyah 1 Kisaran Elementary School. The study used a qualitative approach with a descriptive type. The research subjects consisted of teachers and lower-grade students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that optimizing visual-based media through images, posters, learning videos, picture cards, and presentation slides can increase students' attention, activeness, and understanding of PPKn material. The main findings of the study indicate that visual media helps connect PPKn concepts with everyday experiences so that learning becomes more concrete and meaningful. Despite obstacles such as limited facilities and media preparation time, teachers are able to overcome these through adjusting learning strategies. This study confirms that visual-based media is an effective strategy to improve the quality of PPKn learning in lower grade elementary school students.